Comparison and Explanation of Multiple Strategies: One Example of a Small Step Forward for Improving Mathematics Education. (October 2016) - Star, Jon R.; Rittle-Johnson, Bethany; Durkin, Kelley
Education policy should aim to promote instructional methods that are easy for teachers to implement and have demonstrable, positive impact on student learning. Our research on comparison and explanation of multiple strategies illustrates the promise of this approach. In several short-term experimental, classroom-based studies, comparing different strategies for solving the same problem was particularly effective for promoting student learning. Thus, we developed a supplemental Algebra 1 curriculum to foster comparison in combination with explanation of multiple strategies. In a randomized control trial, teachers used our materials as intended, but much less often than expected, and student learning was not greater in experimental classrooms. Yet greater use of our comparison materials was associated with greater student learning, suggesting the approach has promise when used sufficiently often. These studies provide some evidence that easy-to-implement reforms can change teacher practice and improve student learning.